Українці Словаччини: історико-етнографічний аспект - Сополига, М. (Народна творчість та етнологія, 2017)
У статті досліджено етнічну історію українців Словаччини як автохтонної національної меншини, розглянуто різні наукові теорії щодо походження закарпатських українців, їх національного самовизначення. Проаналізовано чинники впливу на розвиток української спільноти Словаччини (політичні, конфесійні, мовні), розглянуто етнодиференціюючі явища народної матеріальної та духовної культури. У статті констатується українська етнічна належність корінного населення Пряшівщини. В статье исследована этническая история украинцев Словакии как автохтонного национального меньшинства, рассмотрены различные научные теории о происхождении закарпатских украинцев, об их национальном самоопределении. Проанализированы факторы влияния на развитие украинцев Словакии (политические, конфессиональные, языковые), рассмотрены этнодифференцирующие явления народной материальной и духовной культуры. В статье констатируется украинская этническая принадлежность коренного населения Пряшевщины. The article examines the issue of ethnic history of Slovakian Ukrainians as an autochthonous national minority and considers various scientific theories on the origin of Transcarpathian Rusyns and their national self-determination. There is also an analysis of influence factors (political, confessional, and linguistic) concerning the development of Ukrainian community in Slovakia, as well as a consideration of ethno-differentiative phenomena of folk tangible and intangible cultures. The article ascertains the Ukrainian-related ethnic belonging of the Priashivshchyna native population.